Vulnerability and non-adherence to antiretroviral therapy among HIV patients, Minas Gerais State, Brazil Vulnerabilidade e não-adesão à terapia antiretroviral, Minas Gerais, Brasil - Palmira de Fátima Bonolo; Carla Jorge Machado; Cibele Comini César; Maria das Graças Braga Ceccato; Mark Drew Crosland Guimarães (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The aim of the present study was to describe vulnerability profiles and to verify their association with non-adherence to antiretroviral therapy (ART) among 295 HIV-patients receiving their first prescription in two public-referral centers in Minas Gerais States, Brazil. The cumulative incidence of non-adherence was 36.9%. Three pure vulnerability profiles (lower, medium and higher) were identified based on the Grade of Membership method (GoM). Pure type patients of the "higher vulnerability" profile had, when compared to the overall sample, an increased probability of being younger, not understanding the need of ART, having a personal reason to be HIV-tested, not disclosing their HIV status, having more than one (non-regular) sexual partner, reporting use of alcohol, tobacco and illicit drugs, and having sex among men. Non-adherence to ART was statistically associated (p < 0.001) with this profile. Also, the heterogeneity of the sample was found to be high, since over 40% were mixed type. The implications are that health staff should be trained to develop strategies for incorporating risk-reduction interventions, bearing in mind the three dimensions of vulnerability and the diversity of those patients initiating antiretroviral therapy. Este estudo teve como objetivos descrever os perfis de vulnerabilidade e verificar suas associações com a não-adesão à terapia anti-retroviral (TARV) entre os 295 pacientes com HIV que recebiam suas primeiras prescrições em dois serviços públicos de referência de Minas Gerais, Brasil. A incidência cumulativa de não-adesão foi 36,9%. Foram identificados três perfis puros de vulnerabilidade (baixa, média e alta) baseados no método Grade of Membership (GoM). Os tipos puros de pacientes do perfil de "alta vulnerabilidade" tinham, comparados aos outros, probabilidade maior de serem jovens, de não perceberem a necessidade da TARV, de terem uma razão pessoal para realização do teste HIV, de não terem revelado seu status HIV, de terem mais de um (não fixo) parceiro sexual, de relatarem uso de álcool, tabaco e drogas ilícitas e sexo entre homens. Não-adesão à TARV foi associada significativamente a esse perfil (p < 0,001). A heterogeneidade da amostra foi alta, pois mais de 40% dos pacientes eram tipos mistos. Conclui-se que os profissionais de saúde devem ser treinados para desenvolverem estratégias e intervenções de redução de risco, considerando as três dimensões da vulnerabilidade e a diversidade desses pacientes iniciando a TARV.